SOME PHYSICAL PROBLEMS THAT LEAD TO THE BESSEL EQUATION - Berikkhanova Г.Е.; Zholymbayev О.М.; Aniyarov, A. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2023)
In this article consider a second-order differential equation with variable coefficients, which leads to the Bessel equation. As an example, the problems of heat loss through the furnace wall and cylindrical filtration are considered. A mathematical model of these processes has been compiled. The differential equation describing the process is reduced to the Bessel equation. The desired solution is represented as a power series. The Bessel function is also used to solve the problem.